Characterization of the dehydration products due to thermal decomposition of peptides by liquid chromatography‐tandem mass spectrometry. (18th February 2015) - Liu, Chenglin; Topchiy, Elena; Lehmann, Teresa; Basile, Franco
Abstract : Thermal decomposition (TD) of proteins is being investigated as a rapid digestion step for bottom‐up proteomics. Mass spectrometry (MS) analyses of the TD products of simple peptides and intact proteins have revealed several nonvolatile products at masses lower than the precursor biomolecule (M). In addition to products stemming from site‐specific cleavages, many signals are also observed at a corresponding M‐18, most likely because of dehydration (M‐H2 O) during the heating process. Understanding the structural nature of the water loss product is important in establishing the utility of their tandem mass spectra (collision‐induced dissociation) in determining the precursor ion amino acid sequence in a bottom‐up proteomic workflow. Dehydration of a peptide can take place from a variety of sources including side chain groups, C ‐terminus, and/or intramolecular cyclization ( C to N ‐terminus cyclization). In this work, liquid chromatography‐tandem MS (LC‐MS/MS) and a series of standard peptides (angiotensin II, DRVYIHPF and its cyclic analog) are implemented to decipher the structure of the TD dehydration product. In addition, a derivatization strategy incorporating N ‐terminus acetylation was developed that allowed the direct comparison of tandem mass spectra of standard cyclic peptides with those resulting from the TD process, thus eliminating any ambiguity from the direct comparison of their mass spectra (due to gas‐phase cyclization of b ‐ions, which can result in sequence scrambling of the precursor ion). Results from these investigations indicated that peptide dehydrated TD products were mostly linear in nature, and water loss was favored from the C ‐terminus carboxyl group or, when present, the aspartic acid side chain. Given the predictable nature of the formation of TD dehydration products, their MS/MS analysis can be of utility in providing complementary and confirmatory sequence information of the precursor peptide. Copyright © 2015 John Wiley & Sons, Ltd.